2000
DOI: 10.1007/s001980070039
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bone Mineral Density in Older Men

Abstract: Although osteoporosis in men is increasingly recognized as an important health issue and bone mass appears to be a major determinant of fracture, there remain few data concerning the determinants of bone mass in men. To determine the correlates of bone density in men, we studied a large group of older subjects recruited from three rural communities in the northwestern United States. Three hundred and fifty-five men over the age of 60 years (mean 71.5 +/- 7.4 years) without known disorders of mineral metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
4
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 16 publications
7
50
4
4
Order By: Relevance
“…Previous studies have shown lower BMD in patients with trochanteric hip fractures compared with cervical hip fracture patients [19,20]. Since some significant risk factors for trochanteric hip fracture identified in this study are also risk factors for having low BMD, one could speculate that individuals suffering from trochanteric hip fracture may also have low BMD already in middle age [39][40][41][42]. Unfortunately, baseline assessment in this population was done before access to DXA (dual x-ray absorptiometry) and we are therefore unable to evaluate our speculations.…”
Section: Comparison Of Risk Factors For Cervical and Trochanteric Hipmentioning
confidence: 62%
“…Previous studies have shown lower BMD in patients with trochanteric hip fractures compared with cervical hip fracture patients [19,20]. Since some significant risk factors for trochanteric hip fracture identified in this study are also risk factors for having low BMD, one could speculate that individuals suffering from trochanteric hip fracture may also have low BMD already in middle age [39][40][41][42]. Unfortunately, baseline assessment in this population was done before access to DXA (dual x-ray absorptiometry) and we are therefore unable to evaluate our speculations.…”
Section: Comparison Of Risk Factors For Cervical and Trochanteric Hipmentioning
confidence: 62%
“…In these studies, current smokers had greater risk than former smokers at the hip. At the lumbar spine, the risk was similar for current and former smokers [18,28,[30][31][32].…”
Section: Smokingmentioning
confidence: 80%
“…At the hip, there was consistent evidence that BMD declines with age [20][21][22][23][24][25][26][27][28]. In men age 50 to 80 years or older (age range varied by study), in multivariable analyses hip BMD decreased linearly with age at a rate of approximately 1.5-2.5% per decade [20,26] and decreased by up to 5% per decade in univariate analyses [20,25,28]. In longitudinal studies, the crude rate of bone loss (expressed as a percentage of baseline BMD/year) at the hip was approximately 0.3-0.5% per year [21][22][23][24].…”
Section: Advancing Agementioning
confidence: 85%
See 1 more Smart Citation
“…36 In addition, the prevalence potentially may be affected by concurrent osteoarthrosis. Osteoarthrosis involves hypertrophy of the bone and increases apparent BMD without necessarily increasing strength, an observation also reported by Cauley et al 27 in the MrOS Research Group report and by Orwoll et al 37 The competing effects of the expected decline in BMD associated with aging and the expected increase in BMD associated with osteoarthrosis over time may lead to misclassification of men with lumbar osteoporosis as "normal," which may render densitometry less reliable for the diagnosis of lumbar osteoporosis. In effect, this misclassification decreases the observed prevalence of osteoporosis and necessarily increases the NNS to prevent one additional vertebral fracture at any given age.…”
Section: Prevalencementioning
confidence: 86%